2008
DOI: 10.1080/09513590801948341
|View full text |Cite
|
Sign up to set email alerts
|

Increased rate of endometriosis and spontaneous abortion in anin vitrofertilization program: No correlation with epidemiological factors

Abstract: These data suggest but do not prove that the risk of SAB is increased in women with endometriosis. The epidemiological risk factors of endometriosis are not associated with an increase in the abortion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…During pregnancy, an ovarian endometrioma was present in 86% (125) of cases. DIE was present in 12% of patients (18); of these, nine patients had bowel endometriosis, six bladder localization, and three vaginal nodules. Extrapelvic endometriosis was present in 16% of patients (24); of these, five patients had abdominal wall endometriosis, one patient had inguinal localization, and one woman had diaphragmatic endometriosis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…During pregnancy, an ovarian endometrioma was present in 86% (125) of cases. DIE was present in 12% of patients (18); of these, nine patients had bowel endometriosis, six bladder localization, and three vaginal nodules. Extrapelvic endometriosis was present in 16% of patients (24); of these, five patients had abdominal wall endometriosis, one patient had inguinal localization, and one woman had diaphragmatic endometriosis.…”
Section: Resultsmentioning
confidence: 98%
“…The relationship between endometriosis and pregnancy-induced hypertension/preeclampsia is still being debated [15,16]. Conflicting data on the risk of miscarriage have been reported [17,18]; moreover, some authors found a higher incidence of miscarriage in women with ovarian endometriosis compared to other locations of the disease [19]. An increased caesarean section rate in women affected by endometriosis compared to healthy controls has been reported [20].…”
Section: Introductionmentioning
confidence: 99%
“…Investigators disagree about the increased risk of spontaneous pregnancy loss after implantation (Al-Azemi et al 2000; Diaz et al 2000; Matalliotakis et al 2008a, 2008b; Metzger et al 1986; Olive et al 1982; Pittaway et al 1988; Wheeler et al 1983; Yanushpolsky et al 1998). Some studies suggest no increased risk of loss (Al-Azemi et al 2000; Diaz et al 2000; Pittaway et al 1988).…”
Section: Impact On the Uterus: Risk Of Miscarriagementioning
confidence: 99%
“…Secondly, recent publications indicate that endometriosis increases the risk of late miscarriage and preterm birth [10][11][12]. Placental bed biopsy studies by Kim et al [13,14] have shown that preterm birth with or without rupture of the membranes is associated with incomplete transformation of the uteroplacental arteries.…”
mentioning
confidence: 98%